Dialogue et interaction au cœur de la réflexion sur l'acquisition du langage - Salazar Orvig, Anne (My University, 2017)
Interactionist (Vygostki, de Weck) and dialogic (François) approaches of language acquisition assume not only that dialogue and/or interaction play a determinant role in language acquisition, but also that forms and structures cannot be understood without referring to discursive practices. Whereas communicative experience is a central concept in most non nativist approaches, for the needs of arguing or demonstration some aspects may be more often foregrounded than others and the dialogic dimension can end up being unaddressed. After a brief presentation of usage-based approaches, this paper contrasts grammatical acquisitions under the light of cultural and social roles and their expression through activities. In the last section it proposes some hints on the way dialogue (and not simply input) is not only the context but also the vehicle for the acquisition of referring expressions, their referential value and their use.